ENHANCING INTERNAL CONTROL THROUGH THE IMPLEMENTATION OF ACCOUNTING SYSTEMS AND PROCEDURES FOR WORKING CAPITAL CREDIT PROVISION - Tiwuk Puji Hariyanti; Shafa Aulia Shalsa Efendi (Universitas Tulungagung, 2024)
PT. BPR Nusamba Wlingi is one of the many BPRs that are involved in improving people's living standards. PT. BPR Nusamba Wlingi also provides credit facilities that can be utilized by business people as a solution for business or enterprise developers. Credit is the provision of loans or financing by lenders to borrowers with a repayment process that takes place in stages over a period of time agreed by both parties. The method used in this research is a descriptive qualitative approach. In this research, data collection uses observation, interviews and documentation. Data analysis uses data reduction and data presentation. Test the validity of the data using source triangulation. The results of the research can be concluded that(1) the system and procedures for providing working capital credit that have been carried out are quite good with the use of forms and separation of functions having been carried out according to procedures using the 5C principle, namely: Character, Capacity, Capital, Collateral and Condition (2) the internal control system for providing working capital credit is effective. However, there are still multiple job functions found, so additional internal auditor functions are needed and a Surprised Audit is carried out